MENELUSURI KESIAPAN LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Astri Furqani; Rusnani . (Fakultas Ekonomi dan Bisnis, 2020)
Baitul Mal Wat-Tamwil (BMT) is a sharia microfinance institution. The current challenge for BMT is the change in the global business landscape based on the internet and information technology or the so-called industrial revolution 4.0. The phenomenon of the industrial revolution 4.0 must be anticipated by BMT. The purpose of this study is to determine the readiness of BMT in responding to the 4.0 industrial revolution and provide suggestions for improvement. This study used a qualitative approach with a descriptive type case study method of BMT which was used as a research site, namely BMT NU (Nuansa Umat) East Java which was centered in Gapura Tengah Village, Gapura District, Sumenep Regency due to its very rapid development and became the BMT with the largest assets on Madura Island. . The results of the research are the readiness of BMT NU East Java in facing the era of the Industrial Revolution 4.0 when viewed from 6 existing aspects such as aspects of Economic Challenges, Social Challenges, Increased Virtual Performance, Technical Challenges, Environmental Challenges and Regulatory and Political Challenges all have gone very well, however technological developments / service innovations owned by BMT NU are not yet fully familiar among members / customers in utilizing these services so that there is a need for increased relationship management to better know the needs of the community and its members